2021
DOI: 10.1080/17482631.2021.1898317
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant again? Perspectives of adolescent and young mothers who and do not experience a repeat pregnancy in adolescence

Abstract: Introduction: Teen pregnancy remains a major social and public health issue in developing countries. Each additional child compromises the development of both the mother and children. Scarce studies have been performed in Latin America. Purpose: This study explores and analyzes individual and family factors associated with repeat pregnancies during adolescence to better elucidate the phenomenon. Methods: Qualitative-descriptive study. Thirty semi-structured interviews were conducted with mothers 20 years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Teenage pregnancy and parenthood have long history of being viewed as social problems in the United States [ 2 ] Although teenage pregnancy has been discussed and examined over the years, progress is needed in finding effective ways to provide support to pregnant and parenting teenagers [ 22 , 23 ]. We contend that framing teenage pregnancy and parenthood as social problems adversely affects the social support that pregnant and parenting teens receive in their families, schools, and communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teenage pregnancy and parenthood have long history of being viewed as social problems in the United States [ 2 ] Although teenage pregnancy has been discussed and examined over the years, progress is needed in finding effective ways to provide support to pregnant and parenting teenagers [ 22 , 23 ]. We contend that framing teenage pregnancy and parenthood as social problems adversely affects the social support that pregnant and parenting teens receive in their families, schools, and communities.…”
Section: Discussionmentioning
confidence: 99%
“…Renbarger and colleagues used House’s social support theory in a small-scale study to test if all four forms of social support enhanced their health outcomes. They found the maternal and child health outcomes may be improved through providing social support by helping to promote positive and trust-based relationships between the women and their health care providers during the prenatal care process [ 22 ] Studies have also suggested that there needs to be more focus on social support for parenting adolescents, as they are still children themselves, and the parenting aspect may be left out after the pregnancy [ 23 ] In the present study, we explored the pregnant teenagers, teenage parents, and parents who had children as teenagers’ perceptions of the social support they received in their rural community. By documenting where rural pregnant and parenting teens receive social support from and how it has helped them navigate pregnancy and parenting decisions, we aim to inform public health resources for pregnant and parenting teens and their children.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent teenage pregnancy occurs when there is more than one pregnancy before the age of 20 amongst females [ 10 ]. Teenage mothers have about 30%, and 50% chances of becoming pregnant again within a year, and two years after the first pregnancy respectively [ 11 , 12 ]. The care of an additional family member demands extra resources, further deteriorating the quality of life of the mother and her offspring [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…They include poverty, young age of first pregnancy, adolescence marriage, being a child of a teenager, and poor attitude towards family planning among teenagers. [ 10 , 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Para una APEO exitosa, la provisión de servicios de consejería y anticoncepción debe iniciar desde la atención del embarazo (considerando especialmente los anticonceptivos reversibles de acción prolongada, ARAP) y continuar en el periodo posaborto, posparto inmediato o extendido (24 meses), sustentándose en los derechos sexuales y reproductivos (DSR) e involucrando a las parejas y familias. [8][9][10][11] En el contexto mexicano, 98.1% de las gestantes adolescentes recibe atención prenatal y 98.3% de los partos de éstas se atienden institucionalmente. 12 Asimismo, la provisión de APEO en adolescentes se incrementó de 52.4 a 63.6% durante 2012-2016, mientras que la cobertura disminuyó de 77.0% en 2017 a 65.1% en 2020, [13][14][15][16] particularmente en este último año, como consecuencia de disrupciones en la cadena de suministro de métodos anticonceptivos (MA), de la suspensión o reducción de servicios no vinculados directamente a la atención de la pandemia Covid-19, del temor de la población a acudir a los centros de salud y de riesgos de contagios y restricciones de distanciamiento social.…”
Section: Introductionunclassified